2015
DOI: 10.1186/s13705-015-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for modelling the energy flow in food chains

Abstract: Background: The heavy reliance of the global food chain on the use of fossil fuels and anticipated rise in global population threatens future global food security. Due to the complexity of the food and energy systems, the impact of adequate food, climate or energy policies should be carefully examined in a modelling framework which considers the interaction of the food and energy systems. However, due to the different modelling approaches available, it can be very difficult to identify which method best suits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The need for economical management of natural resources and the minimization of negative externalities in line with the Sustainable Development paradigm is of particular importance in the context of accelerating climate change. This increases the pressure to search for solutions that reduce energy consumption and GHG emissions not only in the sphere of food production, but also in general in distribution processes [21,[47][48][49][50][51].…”
Section: Gonçalves and Zeroualmentioning
confidence: 99%
“…The need for economical management of natural resources and the minimization of negative externalities in line with the Sustainable Development paradigm is of particular importance in the context of accelerating climate change. This increases the pressure to search for solutions that reduce energy consumption and GHG emissions not only in the sphere of food production, but also in general in distribution processes [21,[47][48][49][50][51].…”
Section: Gonçalves and Zeroualmentioning
confidence: 99%
“…Bekhet and Abdullah [25] studied the agricultural energy chain in Malaysia, in an attempt to reduce food imports, minimise energy consumption and increase the yield of the agricultural industry. The observations from these previous studies, and from others [26] have shown that input-output models provide an aggregate overview of the energy flow of the sectors in question, allowing the user to analyse inter-industry relationships, with data usually obtained from the same sources (improving data consistency) and providing weights of the individual inputs to the final results allowing the user to determine the most consequential input. However, the main drawbacks are that input-output models tend to stop at demand along the chain, and generally ignore wastes.…”
Section: Analytical Approaches Used In the Literaturementioning
confidence: 99%
“…However, the main drawbacks are that input-output models tend to stop at demand along the chain, and generally ignore wastes. The aggregation of data at high level obtained from input-output tables prevents the determination of process-specific energy hotspots along the chain, and the low frequency of national input-output tables from the government statistics office further introduces uncertainty into the models [26]. The latter drawback increases the difficulty in the creation of trends and model validation.…”
Section: Analytical Approaches Used In the Literaturementioning
confidence: 99%
“…The low temperatures are essential to preserve the food and ensure its quality. However, the cold that they cause must be balanced by the HVAC systems which generally translates in increased use of energy [ 6 ]. Finding the balance point where thermal comfort is available to the costumers and at the same time spending the lowest amount of energy is the objective of the HVAC management [ 7 ].…”
Section: Introductionmentioning
confidence: 99%